PENGARUH PENGGUNAAN Divine Cigarette TERHADAP PERTUMBUHAN RUMPUT LAUT Gracilaria verrucosa (Hudson) Papenfus - Imaniar, Khajar; Sunaryo, Sunaryo; Santosa, Gunawan Widi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Seaweed culture in Indonesia has a good prospects and is very important in the supply of row material at agar industry. Request seaweed for industrial use can met through the culture process. Optimalitation of the seaweed production in marine culture need to pay attention to environmental factors, especially mercury. Pollution of mercury in the water rearing media of seaweed can damage on tissue of plant. The Divine cigarette can catch, control and decay free radicals, may with its application in the process of cultivation very important to do. This research was aimed to know the influence of Divine cigarette on the rearing media to the growth of seaweed G. verrucosa. This research was conducted at the Hatchery of Coastal Ecodevelopment Area Laboratory (LPWP) Prof. Dr. Ir. Gatot Rahardjo Joenoes, the University of Diponegoro, Jepara on June-July 2012. Treatments were the addition of the Divine cigarette in the fertilizer (A) and without Divine cigarette addition (B) on fertilizer rearing in the media of seaweed G. verrucosa. The observation were made on the spesific growth rate of seaweed G. verrucosa and statistically analyzed using t-test. The results of this research showed that the growth respons of G. verrucosa was significantly difference (p<0,05).